Lithium secondary battery

A layered negative electrode structure in lithium secondary batteries controls lithium metal deposition, enhancing cycle characteristics and capacity retention by using a lithium ion-occluding first layer, a lithium metal second layer, and an insulating, ion-permeable third layer to prevent dendrite growth.

JP7620815B2Active Publication Date: 2025-01-24PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021542651
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-08-30
Filing Date
2020-07-28
Publication Date
2025-01-24
Estimated Expiration
2040-07-28

AI Technical Summary

Technical Problem

Lithium secondary batteries face challenges with lithium metal dendrite formation, leading to increased specific surface area and side reactions, which deteriorate discharge capacity and cycle characteristics.

Method used

A layered structure for the negative electrode comprising a lithium ion-occluding first layer, a lithium metal second layer, and an insulating, lithium ion-permeable third layer is introduced to control lithium metal deposition and suppress dendrite growth.

Benefits of technology

The layered structure effectively suppresses lithium metal precipitation between the third layer and the separator, improving cycle characteristics and capacity retention.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007620815000002
    Figure 0007620815000002
  • Figure 0007620815000003
    Figure 0007620815000003
  • Figure 0007620815000004
    Figure 0007620815000004
Patent Text Reader

Abstract

This lithium secondary battery comprises: a positive electrode; a negative electrode; a non-aqueous electrolyte that has lithium ion conductivity; and a separator disposed between the positive electrode and the negative electrode. Lithium metal is deposited on the negative electrode when charging, and the lithium metal melts when discharging. The negative electrode includes a negative electrode current collector, and a plurality of layers stacked on the negative electrode current collector. The plurality of layers include a first layer, a second layer, and a third layer. Of the first to third layers, the first layer is closest to the negative electrode current collector and the third layer is farthest from the negative electrode current collector. The first layer includes a material capable of absorbing lithium ions, the second layer includes lithium metal, and the third layer has insulating properties and lithium ion permeability.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an improvement in lithium secondary batteries. [Background technology]

[0002] Non-aqueous electrolyte secondary batteries are used in ICT such as personal computers and smartphones, in-vehicle batteries, power storage, and other applications, and are in demand for high capacity. Lithium ion batteries are known as high-capacity non-aqueous electrolyte secondary batteries. Lithium ion batteries can be made to have high capacity by using, for example, graphite and an alloy active material in combination as a negative electrode active material. Silicon, silicon compounds, and the like have been proposed as alloy active materials. However, the capacity of lithium ion batteries is reaching its limit.

[0003] Lithium secondary batteries (lithium metal secondary batteries) are promising high-capacity non-aqueous electrolyte secondary batteries that exceed lithium-ion batteries. In lithium secondary batteries, lithium metal precipitates on the negative electrode during charging, and dissolves in the non-aqueous electrolyte during discharging.

[0004] When a lithium secondary battery is charged, lithium metal may precipitate in the form of dendrites on the negative electrode. When dendrites form, the specific surface area of ​​the negative electrode increases, and side reactions tend to increase. As a result, the discharge capacity and cycle characteristics tend to decrease.

[0005] Patent Document 1 proposes that in a lithium electrode including a porous carbon body and lithium metal inserted into the pores of the porous carbon body, a lithium ion conductive protective layer is formed on at least one surface of the lithium electrode.

[0006] Patent Document 2 proposes a lithium metal anode comprising a lithium metal layer and a multi-layer polymer coating on the lithium metal layer, the multi-layer polymer coating comprising a first outer polymer cross-linked gel layer disposed in contact with a battery electrolyte, the first outer polymer cross-linked gel layer comprising a first polymer, a soft segment polymer, and an electrolyte in a cross-linked matrix, and a second inner layer disposed between the lithium metal layer and the first outer polymer cross-linked gel layer, the second inner layer comprising a second polymer that provides mechanical strength and a physical barrier to the lithium metal layer. It is said that the multi-layer polymer coating can inhibit or reduce the growth of lithium dendrites, thereby improving the cycle life of the battery. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Special Publication No. 2015-517853 [Patent Document 2] US Patent Application Publication No. 2016 / 0372743 Summary of the Invention

[0008] In the methods of Patent Documents 1 and 2, lithium metal may precipitate in the form of dendrites between the lithium ion conductive protective layer or the multilayer polymer coating and the separator, making it difficult to sufficiently improve cycle characteristics.

[0009] In view of the above, one aspect of the present invention relates to a lithium secondary battery comprising: a positive electrode, a negative electrode, a lithium ion conductive nonaqueous electrolyte, and a separator disposed between the positive electrode and the negative electrode, in which lithium metal precipitates in the negative electrode during charging and the lithium metal dissolves during discharging, the negative electrode includes a negative electrode current collector and a plurality of layers laminated on the negative electrode current collector, the plurality of layers including a first layer, a second layer, and a third layer, in which, of the first to third layers, the first layer is closest to the negative electrode current collector and the third layer is furthest from the negative electrode current collector, the first layer includes a material capable of absorbing lithium ions, the second layer includes lithium metal, and the third layer is insulating and lithium ion permeable.

[0010] In the lithium secondary battery according to the present invention, the deposition of lithium metal between the third layer and the separator is suppressed, and therefore the cycle characteristics are improved. [Brief description of the drawings]

[0011] [Figure 1] FIG. 2 is a cross-sectional view showing a schematic view of a positive electrode and a negative electrode immediately after assembly of a battery according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view illustrating a schematic diagram of a negative electrode in a charged state according to one embodiment of the present invention. [Diagram 3] FIG. 2 is a cross-sectional view that illustrates a schematic diagram of a negative electrode in a discharged state according to one embodiment of the present invention. [Figure 4] 1 is a vertical cross-sectional view showing a schematic diagram of a lithium secondary battery according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The lithium secondary battery according to this embodiment includes a positive electrode, a negative electrode, a lithium ion conductive non-aqueous electrolyte, and a separator disposed between the positive electrode and the negative electrode. In the negative electrode, lithium metal is precipitated during charging, and the lithium metal is dissolved during discharging. The negative electrode includes a negative electrode current collector and a plurality of layers laminated on the negative electrode current collector. The plurality of layers include a first layer, a second layer, and a third layer. Of the first to third layers, the first layer is the closest to the negative electrode current collector, and the third layer is the farthest from the negative electrode current collector. The first layer includes a material capable of occluding lithium ions. The second layer includes lithium metal. The third layer is insulating and lithium ion permeable.

[0013] The components of a lithium (metal) secondary battery will be described in detail below.

[0014] The negative electrode includes a negative electrode current collector made of a metal that does not react with lithium metal. For example, a metal foil can be used as the negative electrode current collector. Examples of metals constituting the negative electrode current collector include copper (Cu), nickel (Ni), iron (Fe), and alloys containing these metal elements. As alloys, copper alloys, stainless steel (SUS), and the like are preferable. Among them, copper and / or copper alloys are preferable in terms of excellent electrical conductivity. The content of copper in the negative electrode current collector is preferably 50 mass % or more, and may be 80 mass % or more. The thickness of the negative electrode current collector is not particularly limited, and is, for example, 5 μm to 20 μm.

[0015] (1st layer) The first layer is thought to act as an induction layer that attracts lithium ions toward the negative electrode current collector side rather than the third layer during the initial stage of charging. During charging, lithium ions are preferentially absorbed into the first layer. When the first layer is filled with lithium ions, the lithium ions are precipitated on the first layer as lithium metal.

[0016] Only a portion of the charging capacity is related to the material capable of absorbing lithium ions contained in the first layer. Most of the remaining capacity is generated by the dissolution and precipitation of the lithium metal that forms the second layer. Therefore, the first layer can be thin, and the thicker the second layer can be formed, the higher the volumetric energy density of the battery.

[0017] If the first layer does not exist, some of the lithium ions may precipitate on the separator side surface of the third layer during charging. This is thought to be because, if the first layer does not exist, the starting points of lithium metal precipitation are formed unevenly during the first charge, and lithium metal is likely to grow locally. In particular, if there are slight defects in the third layer, lithium metal is likely to grow from such defects as starting points to the separator side surface of the third layer. Such lithium metal is likely to grow as dendrites and become isolated. If lithium metal becomes isolated, it cannot participate in charge and discharge, and the capacity retention rate decreases.

[0018] The material capable of absorbing lithium ions contained in the first layer (hereinafter also referred to as active material) may be, for example, a material that can be used as a negative electrode active material for a lithium ion battery. Specifically, a carbon material capable of electrochemically absorbing and releasing lithium ions, a metal that alloys with lithium, a metal compound, etc. may be used.

[0019] Among these, carbon materials are preferred in terms of low cost. Examples of carbon materials include natural graphite, artificial graphite, non-graphitizable carbon, easily graphitizable carbon, carbon black, and carbon nanotubes.

[0020] A film of a metal that alloys with lithium (hereinafter referred to as a metal film) may be formed as the first layer. A metal film is advantageous in that it is easy to form a thin and uniform first layer and it is easy to attract lithium ions more uniformly to the surface of the first layer.

[0021] Specific examples of metals that form the metal film include aluminum, zinc, silicon, and tin.

[0022] Examples of the metal compound include oxides such as silicon compounds and tin compounds, and spinel compounds such as lithium titanate.

[0023] The thickness of the first layer may be, for example, 20 μm or less, or may be 10 μm or less, when particulate materials such as carbon materials, metal compounds, etc. are used as the active material. In order to more uniformly attract lithium ions to the surface of the first layer, the first layer containing these particulate materials may be 5 μm or more thick.

[0024] When a metal film is formed as the first layer, the thickness of the first layer may be, for example, 1 μm or less, and may be 0.1 μm or less, but in order to more uniformly attract lithium ions to the surface of the first layer, it is preferable that the thickness is 0.01 μm or more.

[0025] The thickness of the first layer is determined as the average value of thicknesses at any five points on the first layer in a cross section of the negative electrode in the thickness direction.

[0026] (2nd layer) Immediately after the battery is assembled, the negative electrode may not have the second layer. During the first charge, lithium ions are absorbed in the first layer, and then lithium metal is precipitated between the first layer and the third layer to form the second layer. The battery may then be designed so that a small thickness of the second layer remains in the fully discharged state. If even a small amount of the second layer exists in the fully discharged state, lithium ions are more likely to penetrate the third layer and be drawn into the second layer during subsequent charging, and are more likely to precipitate so as to uniformly increase the thickness of the second layer. This is thought to be because the second layer stably provides a uniform starting point for further lithium metal precipitation. Thus, the precipitation of lithium metal between the third layer and the separator is suppressed, improving cycle characteristics.

[0027] The fully discharged state of a lithium secondary battery refers to a state in which the battery is discharged to a state of charge (SOC) of 0.05×C or less when the rated capacity of the battery is C. For example, it refers to a state in which the battery is discharged to a lower limit voltage at a constant current of 0.05C. The lower limit voltage is, for example, 2.5V to 3.0V. On the other hand, the fully charged state of a lithium secondary battery refers to a state in which the battery is charged to a state of charge (SOC) of 0.95×C or more when the rated capacity of the battery is C. For example, it refers to a state in which the battery is charged to an upper limit voltage at a constant current of 0.05C.

[0028] The thickness of the second layer may be, for example, 1 to 50 μm, or may be 1 to 30 μm. In a fully discharged state, the second layer may be designed to be thin, for example, 1 to 5 μm or 2 to 5 μm. In a fully charged state, the second layer may be designed to be thick, for example, 10 to 30 μm or 20 to 25 μm.

[0029] The thickness of the second layer is determined as the average thickness of any five points on the second layer in a cross section of the negative electrode in the thickness direction.

[0030] (3rd layer) The third layer is permeable to lithium ions and insulating (electronically insulating). Only lithium ions that penetrate the third layer and reach the surface of the first or second layer receive electrons, and lithium metal is deposited there. Therefore, the deposition of lithium metal on the separator side surface of the third layer is basically suppressed.

[0031] If the third layer did not exist, it would be difficult to control the growth direction of lithium metal during charging, and lithium metal would be more likely to precipitate as dendrites. In order to suppress dendrites, it is necessary to control the precipitation direction of lithium metal by the third layer.

[0032] In addition, if the first layer does not exist, the starting point of lithium metal deposition is not formed stably on the negative electrode current collector, and lithium metal tends to deposit unevenly and locally, which makes it easier for dendrites to grow through the third layer.

[0033] The third layer may be, for example, a porous film made of an insulating material as long as it is insulating and lithium ion permeable. The porous film has pores through which lithium ions can pass. The porous film may have a three-dimensional mesh structure to form continuous pores, or may have through-holes.

[0034] The porous membrane may have, for example, an insulating polymer matrix. The polymer matrix has a pore structure or a network structure that can be swollen with a solvent for the non-aqueous electrolyte. Lithium ions move through the non-aqueous electrolyte held in the matrix.

[0035] The type of insulating polymer is not particularly limited as long as it can form a matrix capable of holding a non-aqueous electrolyte. Examples of polymers that can form a porous membrane include fluororesins such as polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), copolymers of vinylidene fluoride and hexafluoropropylene (VdF-HFP), copolymers of vinylidene fluoride and trifluoroethylene (VdF-TrFE), resins having a polyoxyalkylene structure such as a polyethylene oxide structure, polyacrylonitrile (PAN), polyimide resins, acrylic resins, polyolefin resins, urethane resins, polycarbonate resins, and epoxy resins. Among them, fluororesins are preferable in consideration of chemical stability and affinity with non-aqueous electrolytes.

[0036] Among fluororesins, in terms of swelling with non-aqueous electrolytes, fluororesins having a vinylidene fluoride-derived unit (-CH2-CF2-) are preferred. Examples of fluororesins having a vinylidene fluoride-derived unit include PVdF, VdF-HFP, and VdF-TrFE.

[0037] The porous film may contain at least one selected from the group consisting of lithium salts and room-temperature molten salts. Both the lithium salts and the room-temperature molten salts increase the lithium ion conductivity of the porous film and impart flexibility to the porous film.

[0038] The third layer may be a single layer structure or a multi-layer structure. When each layer constituting the multi-layer structure has a through hole, the lithium ion reaches the surface of the first layer or the second layer through the through hole of each layer and receives the electron. Here, when the third layer has a multi-layer structure, the positions of the through holes of each layer are shifted in many places, and there are almost no through holes that penetrate all layers at the same time. Therefore, even if the lithium metal generated by receiving the electron from the first layer or the second layer enters the through hole and grows, it is difficult for it to grow to the separator side. Therefore, the deposition of the lithium metal on the separator side surface of the third layer is suppressed.

[0039] The diameter of the through-holes is not particularly limited as long as the lithium ions can pass through the through-holes. The average diameter of the through-holes may be, for example, in the range of 100 nm to 1000 nm, or in the range of 200 nm to 800 nm.

[0040] The average diameter of the through holes is the average value of the through holes contained in a 2 mm square area when the main surface of the porous membrane is viewed from its normal direction. The average diameter of the through holes may be calculated from a cross section in the thickness direction of the negative electrode. For example, the average diameter of the through holes is calculated by selecting 10 through holes arbitrarily from a cross section of 10 mm in the thickness direction of the negative electrode, and averaging the widths of these through holes. The width of the through holes is the length in the direction perpendicular to the thickness direction of the negative electrode. A scanning electron microscope (SEM) may be used to measure the width of the through holes.

[0041] A solid electrolyte layer may be formed as the third layer. The solid electrolyte layer may be a dense layer having lithium ion conductivity. As the solid electrolyte, an oxide solid electrolyte, a sulfide solid electrolyte, or the like is used.

[0042] Examples of oxide solid electrolytes include NASICON-type solid electrolytes such as LiTi2(PO4)3 and its elemental substitutes, (LaLi)TiO3-based perovskite-type solid electrolytes, and Li 14 ZnGeO 16, LISICON-type solid electrolytes typified by Li4SiO4, LiGeO4 and their element substitution products, Li7La3Zr2O 12 and garnet-type solid electrolytes typified by their element substitution products can be used.

[0043] As the oxide solid electrolyte, the general formula: Li x MO y (M is at least one selected from the group consisting of B, Al, Si, P, Ti, V, Zr, Nb, Ta and La, and satisfies 0.5 < x ≤ 9, 1 ≤ y < 6.) A polyoxymetallate compound represented by the formula may be used. Examples of the polyoxymetallate compound include Li3PO4, Li2SiO3, Li4SiO4, Li2Si2O5, LiTaO3 and the like.

[0044] As the sulfide solid electrolyte, for example, Li2S-P2S5, Li2S-SiS2, Li2S-B2S3, Li2S-GeS2, Li 3.25 Ge 0.25 P 0.75 S4, Li 10 GeP2S 12 and the like can be used.

[0045] The thickness of the third layer is not particularly limited, but from the viewpoint of increasing the capacity, it is desirable that it is not excessively large. On the other hand, it is desirable that the third layer has a thickness sufficient to withstand the expansion and contraction of the negative electrode accompanying charge and discharge. The thickness of the third layer may be, for example, 5 μm or less, and may be 0.1 μm or more and 5 μm or less, or may be 0.5 μm or more and 2.5 μm or less.

[0046] The thickness of the third layer is determined as the average value of the thicknesses of any five points of the third layer in the cross section in the thickness direction of the negative electrode.

[0047] Usually, the negative electrode is larger than the positive electrode, and a part of the main surface of the negative electrode current collector does not face the positive electrode mixture layer. Lithium metal is likely to deposit on the portion of the negative electrode current collector facing the positive electrode mixture layer. Therefore, the third layer may have a region facing the positive electrode mixture layer (facing region) and a non-facing region not facing the positive electrode mixture layer.

[0048] When the third layer has a facing region and a non-facing region, the contact between the non-facing region of the third layer and the negative electrode current collector can be maintained even in a charged state. Therefore, the distance between the facing region of the third layer and the negative electrode current collector or the first layer is limited, and the lithium metal (second layer) is precipitated while being moderately pressed. The second layer is pressed, and thus the growth of dendrites is suppressed. When the lithium metal precipitates, the growth of the lithium metal is restricted in the thickness (Z-axis) direction of the negative electrode current collector, but is not restricted at all in the plane (XY plane) direction of the negative electrode current collector. In other words, the lithium metal is easily diffused in the XY plane direction and is difficult to diffuse in the Z-axis direction, and the tendency for the growth of dendrites to be suppressed is strengthened.

[0049] 1 is a cross-sectional view showing a schematic diagram of a positive electrode and a negative electrode immediately after the battery according to the present embodiment is assembled. The negative electrode 20 immediately after the battery is assembled includes a negative electrode current collector 21, a first layer 221 formed on the surface of the negative electrode current collector 21, and a third layer 223 formed so as to cover the first layer 221. On the other hand, the positive electrode 10 includes a positive electrode current collector 11 and a positive electrode mixture layer 12 formed on the surface of the positive electrode current collector 11.

[0050] The first layer 221 serves as a base layer for the second layer 222, and is therefore formed so as to face the entire positive electrode mixture layer 12, and has a larger outer shape than the positive electrode mixture layer 12. The third layer 223 has a facing region 223a facing the positive electrode mixture layer 12 and a non-facing region 223b not facing the positive electrode mixture layer 12, and a part of the non-facing region 223b is in contact with the negative electrode current collector 21.

[0051] Fig. 2 is a cross-sectional view that shows a schematic diagram of the negative electrode in a charged state according to the present embodiment. When the lithium secondary battery is charged, as shown in Fig. 2, lithium metal is precipitated as the second layer 222 between the first layer 221 and the third layer 223. At this time, the contact between the negative electrode current collector 21 and the non-facing region 223b of the third layer 223 is maintained. Therefore, as described above, the separation distance between the negative electrode current collector 21 and the facing region 223a of the third layer 223 is limited, and the lithium metal is precipitated while being appropriately pressed.

[0052] FIG. 3 is a cross-sectional view that shows a schematic diagram of the negative electrode in a discharged state according to the present embodiment. When the lithium secondary battery is discharged, lithium metal dissolves from the second layer 222, and the second layer 222 having a small thickness remains between the first layer 221 and the third layer 223 as shown in FIG. 3. The remaining second layer 222 having a small thickness becomes the starting point of lithium metal deposition during the next charge. The second layer 222 is formed uniformly over the entire surface of the first layer 221. Therefore, during the next charge, lithium metal deposits over the entire surface of the second layer 222 so as to uniformly increase the thickness of the second layer 222.

[0053] [How to form the first layer] When the active material is a carbon material, a metal compound, or the like, the first layer can be formed in the same manner as, for example, a conventional negative electrode mixture layer for a lithium ion battery. Specifically, a mixture containing an active material as an essential component and containing a binder, a conductive agent, and the like as optional components is mixed with a liquid component that is a dispersion medium to prepare a slurry. The obtained slurry is applied to at least one main surface of a negative electrode current collector, and the coating is dried to form the first layer. The coating after drying may be rolled to form the first layer.

[0054] Examples of the binder include resin materials, such as fluororesins such as polytetrafluoroethylene (PTFE) and PVdF, polyolefin resins such as polyethylene and polypropylene, polyamide resins such as aramid resin, polyimide and polyamideimide resins, acrylic resins such as polyacrylic acid, polymethyl acrylate and ethylene-acrylic acid copolymer, vinyl resins such as PAN and polyvinyl acetate, polyvinylpyrrolidone, polyethersulfone, and rubber-like materials such as styrene-butadiene copolymer rubber (SBR). These may be used alone or in combination of two or more.

[0055] Examples of conductive agents include carbon blacks such as acetylene black, conductive fibers such as carbon fibers and metal fibers, carbon fluoride, metal powders such as aluminum, conductive whiskers such as zinc oxide and potassium titanate, conductive metal oxides such as titanium oxide, and organic conductive materials such as phenylene derivatives. These may be used alone or in combination of two or more.

[0056] When the active material is a metal and a metal film is formed as the first layer, the first layer may be formed by a thin film formation method such as vapor deposition, sputtering, electrolytic plating, or electroless plating.

[0057] [How to form the third layer] In the case of a porous film, the third layer can be formed, for example, by applying a raw material solution for the third layer to the surface of the first layer and then drying it. The raw material solution contains, for example, an insulating material (or an insulating polymer) and a solvent. Examples of the solvent include N-methyl-2-pyrrolidone (NMP).

[0058] As the solvent, a good solvent having high compatibility with the insulating material used and a poor solvent having low compatibility with the insulating material used may be used.

[0059] When a good solvent and a poor solvent are used, a region containing an insulating material and a good solvent is separated from a region containing a poor solvent in the coating film. The separation causes the region containing the poor solvent to be disposed between the regions containing the insulating material. Then, the solvent is removed by drying to form through holes and even non-through holes between the regions containing the insulating material. For example, the pore size and porosity of the pores of the resulting porous film can be controlled by the type of solvent and the mass ratio of the good solvent and the poor solvent.

[0060] In forming the third layer, at least one selected from the group consisting of lithium salts and room temperature molten salts (hereinafter, also simply referred to as salts) may be used. When a good solvent and a salt are used, a region containing an insulating material, a good solvent, and a salt and having a high concentration of the insulating material is separated from a region containing an insulating material and a good solvent and having a lower concentration of the insulating material in the coating film. Then, the coating film is dried to remove the solvent, thereby forming through holes and even non-through holes corresponding to the region having a lower concentration of the insulating material. At this time, the salt remains in the porous film. For example, the pore size, porosity, etc. of the pores of the resulting porous film are controlled by the type and concentration of the salt.

[0061] The good solvent and the poor solvent may be appropriately selected depending on the insulating material to be used. When a good solvent and a poor solvent are used in combination, the good solvent and the poor solvent may have different boiling points, for example, by 10° C. or more, in order to facilitate the formation of holes.

[0062] As the lithium salt, for example, a known one used in a non-aqueous electrolyte of a lithium secondary battery can be used. Specifically, the anion of the lithium salt is BF4 - , ClO4 - , PF6 - , CF3SO3 - , CF3CO2 - Examples of the anion of the oxalate include an anion of an oxalate, and an anion of an imide, which will be described later as an anion of a room temperature molten salt. The anion of the oxalate may contain boron and / or phosphorus. The anion of the oxalate may be an anion of an oxalate complex. Examples of the anion of the oxalate include difluorooxalate borate (BF2(C2O4) - ), Bis(oxalato)borate (B(C2O4)2 - ), B(CN)2(C2O4) - , PF4(C2O4) - , PF2(C2O4)2 - The lithium salts may be used alone or in combination of two or more kinds.

[0063] The room temperature molten salt is a salt that is liquid at room temperature (20°C to 40°C) and is also called an ionic liquid. The room temperature molten salt may be a salt of an organic onium cation and an imide anion, since pores are easily formed in the room temperature molten salt. The room temperature molten salt may be used alone or in combination of two or more kinds.

[0064] Examples of the organic onium cation include cations derived from aliphatic amines, alicyclic amines, aromatic amines, etc. (e.g., quaternary ammonium cations), as well as nitrogen-containing onium cations such as organic onium cations having a nitrogen-containing heterocycle (i.e., cations derived from cyclic amines); sulfur-containing onium cations; phosphorus-containing onium cations (e.g., quaternary phosphonium cations); etc. The organic onium cation may have a functional group such as a hydroxyl group (-OH) or a silanol group (-Si-OH), or may have a divalent group derived from silanol, etc. (e.g., -SiO-).

[0065] Among them, from the viewpoint of heat resistance, a cation having a nitrogen-containing heterocycle is preferable. Examples of the nitrogen-containing heterocycle skeleton include pyrrolidine, imidazoline, imidazole, pyridine, and piperidine. Specific examples include N-methyl-N-propylpiperidinium cation, N,N,N-trimethyl-N-propylammonium cation, and 1-methyl-1-propylpyrrolidinium cation.

[0066] The anion of imides is N(SO2C m F 2m+1 )(SO2C n F 2n+1 ) -(m and n are each independently an integer of 0 or more). Each of m and n may be 0 to 3, or may be 0, 1, or 2. The anion of the imide is bis(trifluoromethylsulfonyl)imide anion (N(SO2CF3)2 - , TFSI - ), bis(perfluoroethylsulfonyl)imide anion (N(SO2C2F5)2 - ), bis(fluorosulfonyl)imide anion (N(SO2F)2 - In particular, the bis(fluorosulfonyl)imide anion, TFSI - may be also possible.

[0067] The concentration of the salt in the raw material solution is not particularly limited and may be appropriately set in consideration of the pore size, porosity, etc. of the pores of the porous membrane to be formed. For example, the concentration of the salt may be 0.5% by mass to 30% by mass, or 1% by mass to 10% by mass.

[0068] The concentration of the insulating material in the raw material solution is not particularly limited and may be appropriately set in consideration of the thickness of the porous film to be formed, etc. The concentration of the insulating material may be, for example, 3% by mass to 35% by mass, or 5% by mass to 15% by mass.

[0069] When the third layer is a solid electrolyte layer, for example, the solid electrolyte layer can be formed by exposing the surface of the first layer to an atmosphere containing raw materials for the solid electrolyte. The atmosphere containing the raw materials for the solid electrolyte is preferably at 200° C. or less, more preferably at 120° C. or less. The solid electrolyte layer is preferably formed by a liquid phase method or a gas phase method.

[0070] Preferred liquid phase methods include a precipitation method, a sol-gel method, etc. These methods include, for example, a process of immersing a negative electrode current collector on which a first layer is formed in a solution at a temperature sufficiently lower than 200° C. in which a raw material of a solid electrolyte is dissolved, and precipitating or depositing a solid electrolyte or its precursor gel on the surface of the first layer.

[0071] Examples of gas-phase methods include physical vapor deposition (PVD), chemical vapor deposition (CVD), and atomic layer deposition (ALD). PVD and CVD are usually performed at high temperatures exceeding 200°C. In the ALD method, a solid electrolyte layer can be formed in an atmosphere containing raw materials for the solid electrolyte at 200°C or less, or even 120°C or less. In the ALD method, organic compounds with high vapor pressure are used as raw materials for the solid electrolyte. By vaporizing such raw materials, the molecular raw materials can interact with the surface of the first layer.

[0072] [Positive electrode] The positive electrode comprises a positive electrode mixture layer containing a positive electrode active material and a positive electrode current collector. The positive electrode mixture layer can be formed by applying a positive electrode slurry, in which a positive electrode mixture containing a positive electrode active material, a binder, a conductive agent, etc. is dispersed in a dispersion medium, to the surface of the positive electrode current collector and drying it. The coating film after drying may be rolled as necessary. The positive electrode mixture layer may be formed on one surface of the positive electrode current collector or on both surfaces.

[0073] When the positive electrode active material contains a composite oxide containing lithium and a transition metal, the total amount of lithium contained in the positive electrode and the negative electrode M Li and the amount of transition metal in the positive electrode, M TM Molar ratio to: M Li / M TM may be 1.1 or less. In other words, in a lithium secondary battery (lithium metal secondary battery), most (or all) of the lithium involved in charging and discharging is derived from the composite oxide containing lithium and a transition metal, which is the positive electrode active material.

[0074] Here, the total amount of lithium contained in the positive electrode and the negative electrode M Li The total amount of lithium contained in the positive electrode mixture layer per unit area and the negative electrode (more specifically, the total of the first layer and the second layer) per unit area facing the positive electrode mixture layer is referred to as the total amount of lithium contained in the positive electrode mixture layer per unit area and the negative electrode (more specifically, the total of the first layer and the second layer) per unit area facing the positive electrode mixture layer. TM This refers to the amount of transition metal contained in the positive electrode mixture layer per unit area.

[0075] The molar ratio of lithium to transition metal contained in the composite oxide: lithium / transition metal may be, for example, 0.9 to 1.1.

[0076] Examples of such a positive electrode active material include layered rock salt type composite oxides. Specifically, as the positive electrode active material, for example, Li a CoO2, Li a NiO2, Li a MnO2, Li a Co b Ni 1-b O2, Li a Co b M 1-b O c (M is at least one selected from the group consisting of Na, Mg, Sc, Y, Mn, Fe, Ni, Cu, Zn, Al, Cr, Pb, Sb, and B), Li a Ni b M 1-b O c (M is at least one selected from the group consisting of Na, Mg, Sc, Y, Mn, Fe, Co, Cu, Zn, Al, Cr, Pb, Sb, and B), LiMPO 4、 (M is at least one selected from the group consisting of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, and B) may be mentioned. Here, 0 < a ≤ 1.1, 0 ≤ b ≤ 0.9, and 2 ≤ c ≤ 2.3. Note that the a value indicating the molar ratio of lithium increases or decreases by charge and discharge.

[0077] Among them, a layered rock salt type composite oxide containing nickel element is preferable. Such a composite oxide is represented by Li a Ni x M 1-x O2 (M is at least one selected from the group consisting of Mn, Co, and Al, and satisfies 0 < a ≤ 1.1, 0.3 ≤ x ≤ 1). From the viewpoint of increasing the capacity, it is preferable to satisfy 0.85 ≤ x ≤ 1. Further, from the viewpoint of the stability of the crystal structure, a lithium-nickel-cobalt-aluminum composite oxide (NCA) containing Co and Al as M: Li a Ni x Co y Al zO2(0 < a ≤ 1.1, 0.85 < x < 1, 0 < y < 0.15, 0 < z ≤ 0.1, x + y + z = 1) is more preferable. Specific examples of NCA include LiNi 0.8 Co 0.15 Al 0.05 O2, LiNi 0.8 Co 0.18 Al 0.02 O2, LiNi 0.9 Co 0.05 Al 0.05 O2 and the like can be mentioned.

[0078] Examples of the binder include resin materials such as fluororesins such as PTFE and PVdF; polyolefin resins such as polyethylene and polypropylene; polyamide resins such as aramid resins; polyimide resins such as polyimide and polyamideimide; acrylic resins such as polyacrylic acid, methyl polyacrylate, and ethylene-acrylic acid copolymer; vinyl resins such as PAN and polyvinyl acetate; polyvinylpyrrolidone; polyethersulfone; rubber-like materials such as styrene-butadiene copolymer rubber (SBR). These may be used alone or in combination of two or more.

[0079] Examples of the conductive agent include graphite such as natural graphite and artificial graphite; carbon blacks such as acetylene black; conductive fibers such as carbon fibers and metal fibers; carbon fluoride; metal powders such as aluminum; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and organic conductive materials such as phenylene derivatives. These may be used alone or in combination of two or more.

[0080] The shape and thickness of the positive electrode current collector can be selected from the shape and range according to the negative electrode current collector, respectively. Examples of the material of the positive electrode current collector include stainless steel, aluminum (Al), aluminum alloy, titanium, and the like.

[0081] [Non-aqueous electrolyte] The non-aqueous electrolyte used has lithium ion conductivity. Such a non-aqueous electrolyte contains a non-aqueous solvent and lithium ions and anions dissolved in the non-aqueous solvent. The non-aqueous electrolyte may be in a liquid state or a gel state.

[0082] The liquid non-aqueous electrolyte is prepared by dissolving a lithium salt in a non-aqueous solvent. When the lithium salt is dissolved in the non-aqueous solvent, lithium ions and anions are generated, but the non-aqueous electrolyte may contain undissociated lithium salt.

[0083] The gelled non-aqueous electrolyte contains a liquid non-aqueous electrolyte and a matrix polymer. For example, a polymer material that absorbs a non-aqueous solvent and gels is used as the matrix polymer. Examples of such polymer materials include fluororesin, acrylic resin, and / or polyether resin.

[0084] The lithium salt may be any known lithium salt used in the non-aqueous electrolyte of a lithium secondary battery.Specifically, the lithium salt may be any of the compounds exemplified as the lithium salt used in the formation of a porous membrane.The non-aqueous electrolyte may contain one or more of these lithium salts.

[0085] In order to further suppress the deposition of lithium metal in the form of dendrites, the non-aqueous electrolyte may contain at least one of an imide anion and an oxalate anion. In particular, an oxalate anion containing boron is preferred. The oxalate anion containing boron may be used in combination with other anions. The other anions may be PF6 - and / or the anion of an imide.

[0086] The concentration of the lithium salt in the non-aqueous electrolyte may be, for example, 0.5 mol / L or more and 3.5 mol / L or less. The concentration of the lithium salt is the sum of the concentration of the dissociated lithium salt and the concentration of the undissociated lithium salt. The concentration of the anion in the non-aqueous electrolyte may be 0.5 mol / L or more and 3.5 mol / L or less.

[0087] Examples of the non-aqueous solvent include esters, ethers, nitriles, amides, and halogen-substituted products thereof. The non-aqueous electrolyte may contain one or more of these non-aqueous solvents. Examples of the halogen-substituted products include fluorides.

[0088] Examples of the ester include carbonate esters and carboxylate esters. Examples of the cyclic carbonate esters include ethylene carbonate, propylene carbonate, vinylene carbonate (VC), and fluoroethylene carbonate (FEC). Examples of the chain carbonate esters include dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and diethyl carbonate. Examples of the cyclic carboxylate esters include γ-butyrolactone and γ-valerolactone. Examples of the chain carboxylate esters include ethyl acetate, methyl propionate, and methyl fluoropropionate. Among these, it is preferable to use at least one of vinylene carbonate (VC) and fluoroethylene carbonate (FEC) from the viewpoint of charge / discharge efficiency.

[0089] Examples of the ether include cyclic ethers and chain ethers. Examples of the cyclic ethers include 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, and 2-methyltetrahydrofuran. Examples of the chain ethers include 1,2-dimethoxyethane, diethyl ether, ethyl vinyl ether, methyl phenyl ether, benzyl ethyl ether, diphenyl ether, dibenzyl ether, 1,2-diethoxyethane, and diethylene glycol dimethyl ether.

[0090] Examples of the nitrile include acetonitrile, propionitrile, benzonitrile, etc. Examples of the amide include dimethylformamide, dimethylacetamide, etc.

[0091] [Separator] A separator is interposed between the positive electrode and the negative electrode. The separator has high ion permeability and has appropriate mechanical strength and insulation properties. As the separator, a microporous thin film, a woven fabric, a nonwoven fabric, etc. can be used. As the material of the separator, polyolefin such as polypropylene and polyethylene is preferable.

[0092] [Lithium secondary battery] FIG. 3 is a vertical sectional view of an example of a cylindrical lithium secondary battery according to one embodiment of the present invention.

[0093] The lithium secondary battery 100 is a wound type battery including a wound electrode group 40 and a non-aqueous electrolyte (not shown). The wound electrode group 40 includes a strip-shaped positive electrode 10, a strip-shaped negative electrode 20, and a separator 30. A positive electrode lead 13 is connected to the positive electrode 10, and a negative electrode lead 23 is connected to the negative electrode 20.

[0094] The positive electrode lead 13 has one end connected to the positive electrode 10 in the length direction, and the other end connected to the sealing plate 90. The sealing plate 90 is provided with a positive electrode terminal 15. The negative electrode lead 23 has one end connected to the negative electrode 20, and the other end connected to the bottom of the battery case 70, which serves as the negative electrode terminal. The battery case 70 is a cylindrical battery can with a bottom, one end in the length direction is open, and the bottom of the other end serves as the negative electrode terminal. The battery case (battery can) 70 is made of metal, for example, iron. The inner surface of the iron battery case 70 is usually nickel-plated. An upper insulating ring 80 and a lower insulating ring 60, which are made of resin, are arranged above and below the wound electrode group 40, respectively.

[0095] In the illustrated example, a cylindrical lithium secondary battery having a wound electrode group has been described, but the present embodiment is not limited to this case and can be applied to other types of lithium secondary battery. The shape of the lithium secondary battery can be appropriately selected from various shapes such as a cylindrical shape, a coin shape, a square shape, a sheet shape, and a flat shape depending on the application. The shape of the electrode group is not particularly limited, and may be a laminated type. In addition, the configuration of the lithium secondary battery other than the negative electrode may be a known one without any particular limitation.

[0096] The present invention will be specifically described below based on examples and comparative examples, but the present invention is not limited to the following examples.

[0097] [Example 1] (1) Preparation of the positive electrode Lithium nickel composite oxide (LiNi 0.8 Co 0.18 Al 0.02 O2), acetylene black, and PVdF were mixed in a mass ratio of 95:2.5:2.5, NMP was added, and the mixture was stirred using a mixer (TK Hivismix, manufactured by Primix Corporation) to prepare a positive electrode slurry. Next, the positive electrode slurry was applied to the surface of an Al foil, the coating was dried, and then rolled to apply a 3.6 g / cm2 density slurry to both sides of the Al foil. 3 A positive electrode having a positive electrode mixture layer of the above formula was fabricated.

[0098] (2) Preparation of the negative electrode (i) Negative electrode current collector An electrolytic copper foil (thickness: 10 μm) was cut to a predetermined electrode size to obtain a negative electrode current collector.

[0099] (ii) 1st layer The active material, artificial graphite (average particle size 3 μm), acetylene black, and PVdF, were mixed in a mass ratio of 90:3:7, and NMP was added, followed by stirring using a mixer (TK Hivismix, manufactured by Primix Corporation) to prepare a slurry. Next, the slurry was applied to the surface of the negative electrode current collector, and the coating was dried and then rolled to form a first layer on both sides of the negative electrode current collector.

[0100] (iii) Third layer A raw material solution containing PVdF (concentration 8% by mass) and NMP was prepared. The raw material solution was applied to both main surfaces of the first layer, and then dried with hot air to form a porous film having a thickness of 3 μm as the third layer.

[0101] A cross section of the obtained negative electrode in the thickness direction was observed by SEM, and it was confirmed that a plurality of through-holes having an average diameter of 800 nm were formed in the third layer.

[0102] (3) Preparation of non-aqueous electrolyte FEC, EMC, and DMC were mixed in a volume ratio of 20:5:75. Lithium difluorooxalatoborate and LiPF6 were dissolved in the resulting mixed solvent to give concentrations of 0.3 mol / L and 1.0 mol / L, respectively, to prepare a nonaqueous electrolyte.

[0103] (4) Battery construction An Al tab was attached to the positive electrode obtained above. A Ni tab was attached to the negative electrode obtained above. In an inert gas atmosphere, the positive electrode and the negative electrode were spirally wound with a polyethylene thin film (separator) interposed therebetween to prepare a wound-type electrode body. The obtained electrode body was housed in a bag-shaped exterior body formed of a laminate sheet having an Al layer, and the nonaqueous electrolyte was injected, and then the exterior body was sealed to prepare a lithium secondary battery A1.

[0104] [Example 2] A lithium secondary battery A2 was produced in the same manner as in Example 1, except that in the third layer formation step, a raw material solution containing PVdF (concentration 8 mass%), LiFSI (referred to as LFSI in Table 1) (concentration 1 mass%) and NMP was used to form a 3 μm-thick porous film as the third layer on both main surfaces of the first layer.

[0105] [Example 3] A lithium secondary battery A3 was produced in the same manner as in Example 2, except that in the first layer formation step, a slurry containing artificial graphite was not used, and an aluminum film having a thickness of 0.1 μm was formed on both sides of the negative electrode current collector by a sputtering method.

[0106] [Example 4] A lithium secondary battery A4 was produced in the same manner as in Example 3, except that in the step of forming the first layer, the thickness of the aluminum film was changed to 0.01 μm.

[0107] [Example 5] A lithium secondary battery A5 was produced in the same manner as in Example 4, except that in the step of forming the third layer, the thickness of the porous film was changed to 5 μm.

[0108] [Comparative Example 1] A lithium secondary battery R1 was produced in the same manner as in Example 1, except that the first layer and the third layer were not provided on the negative electrode current collector.

[0109] [Comparative Example 2] A lithium secondary battery R3 was produced in the same manner as in Example 1, except that the third layer was not provided on the negative electrode current collector.

[0110] [Comparative Example 3] A lithium secondary battery R3 was produced in the same manner as in Example 3, except that the third layer was not provided on the negative electrode current collector.

[0111] [Comparative Example 4] A lithium secondary battery R4 was produced in the same manner as in Example 4, except that the third layer was not provided on the negative electrode current collector.

[0112] [Comparative Example 5] A lithium secondary battery R5 was produced in the same manner as in Example 1, except that the first layer was not provided on the negative electrode current collector.

[0113] [Comparative Example 6] A lithium secondary battery R6 was produced in the same manner as in Example 2, except that the first layer was not provided on the negative electrode current collector.

[0114] [evaluation] A charge / discharge test was carried out on the obtained batteries A1 to A5 and R1 to R6.

[0115] In the charge / discharge test, the battery was charged under the following conditions in a thermostatic chamber at 25°C, then rested for 20 minutes and discharged under the following conditions. This charge / discharge cycle was counted as one cycle, and the charge / discharge test was performed for 50 cycles. The capacity retention rate (%) was calculated by dividing the discharge capacity at the 50th cycle by the discharge capacity at the 1st cycle. The evaluation results are shown in Table 1.

[0116] (Charging) The battery was charged at a constant current of 20 mA until the battery voltage reached 4.1 V, and then was charged at a constant voltage of 4.1 V until the current value reached 2 mA.

[0117] (Discharge) The battery was discharged at a constant current of 20 mA until the battery voltage reached 3.0 V.

[0118] [Table 1]

[0119] In Table 1, when the negative electrode has the first layer and the third layer, the capacity retention rate is significantly improved compared to when the negative electrode has neither the first layer nor the third layer. On the other hand, when the negative electrode has only the first layer, although some comparative examples show a slight improvement in the capacity retention rate, such an improvement effect is insufficient. Furthermore, it can be seen that when the negative electrode has only the third layer, the capacity retention rate may be impaired.

[0120] In the above examples, a porous membrane was formed as the third layer, but it is believed that similar results can be obtained when another type of third layer (e.g., a solid electrolyte layer) is formed. [Industrial Applicability]

[0121] Since the lithium secondary battery according to the present invention has excellent cycle characteristics, it can be used in electronic devices such as mobile phones, smartphones, and tablet terminals, electric vehicles including hybrids and plug-in hybrids, and home storage batteries combined with solar cells. [Explanation of symbols]

[0122] 10 positive electrode 11 Positive electrode current collector 12 Positive electrode mixture layer 13 Positive lead 15 Positive terminal 20 negative electrode 21 Negative electrode current collector 221 1st layer 222 2nd layer 223 3rd layer 223a Opposing area 223b Non-opposed area 23 Negative lead 30 Separator 40 Wound electrode group 60 Lower insulation ring 70 Battery case 80 Upper insulation ring 90 Sealing plate 100 Lithium secondary battery

Claims

1. A battery comprising a positive electrode, a negative electrode, a lithium ion conductive non-aqueous electrolyte, and a separator disposed between the positive electrode and the negative electrode; The positive electrode includes a positive electrode mixture layer including a positive electrode active material and a positive electrode current collector, In the negative electrode, lithium metal is precipitated during charging, and the lithium metal is dissolved during discharging, the negative electrode includes a negative electrode current collector and a plurality of layers laminated on the negative electrode current collector, the plurality of layers includes a first layer, a second layer, and a third layer; Among the first to third layers, the first layer is closest to the negative electrode current collector, and the third layer is farthest from the negative electrode current collector; the first layer includes a material capable of absorbing lithium ions; the second layer comprises lithium metal; the third layer is insulating and lithium ion permeable; the third layer has a facing region facing the positive electrode mixture layer and a non-facing region not facing the positive electrode mixture layer, at least a portion of the non-facing region is in contact with the negative electrode current collector in a charged state.

2. 2. The lithium secondary battery according to claim 1, wherein the first layer has a thickness of 10 μm or less.

3. 3. The lithium secondary battery according to claim 1, wherein the material capable of absorbing lithium ions is a carbon material.

4. 3. The lithium secondary battery according to claim 1, wherein the material capable of absorbing lithium ions is a metal that is alloyed with lithium.

5. 5. The lithium secondary battery according to claim 1, wherein the second layer has a thickness of 1 to 50 μm.

6. 6. The lithium secondary battery according to claim 1, wherein the third layer has a thickness of 5 μm or less.

7. 7. The lithium secondary battery according to claim 1, wherein the third layer is a porous film.

8. The lithium secondary battery according to claim 7 , wherein the porous film has a polymer matrix having units derived from vinylidene fluoride.

9. 9. The lithium secondary battery according to claim 7, wherein the porous film contains at least one selected from the group consisting of lithium salts and room-temperature molten salts.

10. The positive electrode active material includes a composite oxide containing lithium and a transition metal, The total amount of lithium contained in the positive electrode and the negative electrode M Li and the amount M of the transition metal contained in the positive electrode. TM Molar ratio with: M Li / M TM The lithium secondary battery according to any one of claims 1 to 9, wherein is 1.1 or less.

11. 11. The lithium secondary battery according to claim 1, wherein the non-aqueous electrolyte contains at least one of fluoroethylene carbonate and vinylene carbonate.

12. The non-aqueous electrolyte contains lithium ions and anions, The lithium secondary battery according to any one of claims 1 to 11, wherein the anion includes at least one selected from the group consisting of imide anions and oxalate anions.

13. The lithium secondary battery according to claim 12, wherein the anion of the imide is at least one of a bis(fluorosulfonyl)imide anion and a bistrifluoromethylsulfonylimide anion.

Citation Information

Patent Citations

  • Nonaqueous electrolyte battery

    JP2002343437A

  • Nonaqueous secondary battery and charging method therefor

    JP2005251472A

  • Connection device

    JP2015517853A

  • Lithium electrode and lithium secondary battery containing the same

    JP2016527679A

  • Lithium secondary battery with lithium metal formed on the positive electrode and its manufacturing method

    JP2019505971A